2017
DOI: 10.1093/jjco/hyx039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of extended prostate biopsy including apical anterior region for cancer detection and prediction of surgical margin status for radical prostatectomy

Abstract: Objectives: We investigated diagnostic yield of initial biopsy and repeated biopsy including apical cores. Methods: We investigated 573 consecutive men with PSA of ≤20 ng/ml who underwent prostate biopsy between 2004 and 2013. The initial 14-core biopsy consisted of the sextant type, lateral sites at the base and middle, lateral apices (la) at anterior horn sites, and apical anterior sites (aa). The repeated 18-core biopsy consisted of the initial 14-core biopsy with four transition zone (TZ) sites at the base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Moreover, it is important to know the risk of apical PSM before surgery 18 . According to the results of the current study, the rate of a positive apical margin, which has been shown to have a higher recurrence risk than other margins 19 , was significantly increased in men with a positive AL biopsy, consistent with a previous study 20 . On the basis of these data, during nerve-sparing radical prostatectomy, apical dissection of the prostate should be carefully performed in men with a positive AL biopsy to reduce the probability of PSM.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, it is important to know the risk of apical PSM before surgery 18 . According to the results of the current study, the rate of a positive apical margin, which has been shown to have a higher recurrence risk than other margins 19 , was significantly increased in men with a positive AL biopsy, consistent with a previous study 20 . On the basis of these data, during nerve-sparing radical prostatectomy, apical dissection of the prostate should be carefully performed in men with a positive AL biopsy to reduce the probability of PSM.…”
Section: Discussionsupporting
confidence: 92%
“…[1113] The location of tumor in different prostate zone might also influence the status of surgical margin. [14] However, these factors could not fully predict the occurrence of PSM. Therefore, it is critical to find out more accurate preoperative predictors to evaluate the incidence of PSM and to take some measures to minimize it.…”
Section: Introductionmentioning
confidence: 99%